(untitled) (Journal of Science and Technology, 2016)
Levels of some heavy metals in soil and vegetation along a major highway in Libya were determined by Atomic Absorption Spectrophotometry. The concentrations of Pb, Cd, Ni, Zn, Cu, Cr and Mn in soil and vegetation all decreased with distance from the road, indicating their relation to traffic. The concentrations of the metals also decreased with depth in the soil profile indicating that the source of the metals was aerial deposition from motor vehicles. Inter-relationships between metals in the soil were highly significant (p < 0.05) suggesting a common source for these metals. Pb and Zn were found to be deposited more than the other metals. Average values for citrus limon leaves were generally 30 - 65 % of those for Olea europaea leaves. In most cases, between 20-40% of the metals was removable by simple washing with water, indicating that a significant, but not predominant fraction of the metals is in the form of easily-removed particulate matter. Discussion of the results of this study is based on statistical treatment of the data.